1949
DOI: 10.1002/andp.19494400105
|View full text |Cite
|
Sign up to set email alerts
|

Uber die photoelektrischen Eigenschaften von Kadmiumsulfid‐Einkristallen

Abstract: InhaltsiibersichtDie Eigenschaften der Photoleituiig lsei Cadmiumsulfid-Einkristalleii lassen sich gut auf Grund des R i e h l -Schouscheii Energiebandermodells interpretieren, u-enn man auf die Photoelektronen die Begriffe der metallischen Leitung an! wendet. Der Verstarkungseffekt wird auf einen Rauinladungseffekt vor der Kathode zuriickgefiihrt, der erst eine rnetallahnliche Leitung erinoglicht. Es lafit sich eine Beziehung zwischeii Photostroni, Absorptionskoeffizieiit uiid Sc,hichtdicke ableiten, die eine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1950
1950
1968
1968

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This fact was discussed in the past by Fassbender and DeVore. Fassbender [25] assumed bimolecular recombination to occur due to the high excitation rate in the intrinsic absorption region, but this should lead to a slope n = 112 of the photocurrent-illumination characteristic which was experimentally not observed. DeVore [26] proposed surface recombination to cause low photoconductivity in this region, and really, this concept is a well-established one for Ge and Si, but not for CdS.…”
Section: The Properties Of the Surface Space-charge Layer As Revealedmentioning
confidence: 99%
“…This fact was discussed in the past by Fassbender and DeVore. Fassbender [25] assumed bimolecular recombination to occur due to the high excitation rate in the intrinsic absorption region, but this should lead to a slope n = 112 of the photocurrent-illumination characteristic which was experimentally not observed. DeVore [26] proposed surface recombination to cause low photoconductivity in this region, and really, this concept is a well-established one for Ge and Si, but not for CdS.…”
Section: The Properties Of the Surface Space-charge Layer As Revealedmentioning
confidence: 99%
“…In the case of quenching, a transient increase in photoconductivity immediately after the application of far red light is followed by decay. Many authors have reported quenching of photoconductivity of inorganic phosphors by infrared light, as well as some stimulation phenomena of a transient character (35)(36)(37)(38)(39). To explain the rapid transient stimulation, followed by quenching, as observed in CdS, Rose (40) has proposed a model which involves the creation of free holes by infrared radiation.…”
mentioning
confidence: 99%